Institutional Framework as a Determinant of Variations in Service Quality Between Public and Private Hospitals in Tanzania - Raphael Habi; Emmanuel Matiku (Annales Universitatis Mariae Curie-Skłodowska Sectio H, Oeconomia, 2023)
Purpose of the article: This study was set to determine the influence of institutional framework on service quality in both private and public hospitals. The paper sought to establish the perception of respondents regarding the institutional factors that explain the existence of variations in service quality between public and private hospitals. The institutional framework aspects that were considered in comparing health service quality in public and private hospitals were: institutional culture, control, stability and structure. A descriptive survey design was used because the study sought to know the perception of respondents regarding the factors that influence quality of service in hospitals.